Kedudukan Filsafat Ilmu sebagai Landasan Ilmu untuk Pengembagan Teori Manajemen Pendidikan Islam - Nurlaili Muiz, Rizqi; Dhiaulhaq Rahman , Zaky; Sarmain; Fauzi , Anis; Hidayat , Wahyu (Universitas Muhammadiyah Prof Dr Hamka, 2024)
Philosophy of science, which literally means the love of wisdom, has an important role in building the theoretical foundation for various disciplines, including Islamic education management. In this context, the philosophy of science helps to integrate Islamic principles with the demands of modern science, so that it can answer global challenges in education. This study aims to analyze the position of philosophy of science as a foundation in the development of Islamic educational management theory, as well as understand how philosophy of science provides a strong theoretical framework to build educational management theory that is in accordance with the characteristics and mission of Islamic education. This research uses a library research approach by examining various literature related to the philosophy of science and Islamic education management. The results of the study show that the philosophy of science functions as the foundation of ontology, epistemology, and axiology in the development of Islamic education management theory. The philosophy of science helps explain the nature of knowledge, how to acquire knowledge, and the values that underlie the practice of educational management. This research makes an important contribution to understanding the role of philosophy of science in building an effective and efficient theory of Islamic education management. With the foundation of philosophy of science, the development of Islamic educational management theory can be carried out scientifically and systematically, ensuring its relevance in the contemporary context without losing Islamic characteristics.